PERAN SISWA DALAM PENDIDIKAN LINGKUNGAN HIDUP MELALUI PROGRAM ADIWIYATA DI MAN SUMENEP DALAM MENYONGSONG ERA SOCIETY 5.0 - Mochammad Ronaldy Aji Saputra; Heri Budianto (Kariman: Jurnal Pendidikan Keislaman, 2022)
This study aims to determine the role of students in environmental education which is carried out through the Adiwiyata program at MAN Sumenep. This study uses a qualitative method. Data collection techniques used observations, interviews, and documentation. Data analysis was carried out using the Miles & Huberman model, namely data reduction, data presentation, and data conclusion. The results showed that students play an important role in the implementation of environmental education through the Adiwiyata program. For example, students turn off the fan in class after use, bring their own shopping bags from home when shopping in the canteen, plant trees and gardens, and manage waste by applying the 3R principles: Reduce, Reuse, and Recycle, reduce fuel use by using a bicycle. or walking to the madrasa, reducing paper use, making compost from dry leaves, and sorting organic and inorganic waste. The role of students also uses virtual media, namely using Instagram and YouTube to support the Adiwiyata program.